2015
DOI: 10.1097/maj.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to High-Risk Medications is Associated With Worse Outcomes in Older Veterans With Chronic Pain

Abstract: Background Chronic pain is common, costly, and leads to significant morbidity in older adults, yet we have limited data on medication safety. We sought to evaluate the association of incident High Risk Medication in the Elderly (HRME) with mortality, emergency department (ED) or hospital care among older adults with chronic pain. Methods A retrospective Veterans Health Administration cohort study was conducted examining older Veterans with chronic pain diagnoses and use of incident HRME (opioids, skeletal mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Our findings reflect exploratory evidence that should be interpreted with caution and not considered as confirmatory as the factors selected for this secondary analysis were based on theory and previous research. 59 For example, lower education level 8, 16, 76 and increased number of pain medications 23, 51 have demonstrated prognostic capabilities for musculoskeletal pain related clinical outcomes in previous studies, however were only identified as having weak evidence to modify treatment response in our analysis. Future studies are required to confirm these findings prior to changes in clinical practice.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our findings reflect exploratory evidence that should be interpreted with caution and not considered as confirmatory as the factors selected for this secondary analysis were based on theory and previous research. 59 For example, lower education level 8, 16, 76 and increased number of pain medications 23, 51 have demonstrated prognostic capabilities for musculoskeletal pain related clinical outcomes in previous studies, however were only identified as having weak evidence to modify treatment response in our analysis. Future studies are required to confirm these findings prior to changes in clinical practice.…”
Section: Discussionmentioning
confidence: 96%
“…28 Gurung, et al 28 identified younger age, being employed or in sedentary occupations, less narcotic medication use, higher levels of education, and greater positive treatment expectations as potential treatment effect modifiers for positive LBP treatment response using data generated from four randomized trials. In addition, prognostic capabilities associated with lower education level 8, 16, 76 and using an increased number of pain medications 23, 51 have been reported for musculoskeletal pain clinical outcomes in previous studies that have not specifically tested for treatment effect modification. Collectively, our findings support the need for further exploration of treatment effect modification through adequately powered studies and these should include patient level factors such as education level and use of pain medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inappropriate prescriptions [97][98][99][100] and potential prescription omissions [98] have also been documented. Moreover, multiple medications are frequently used in patients with PTSD and traumatic brain injury [101,102], as well as in the management of chronic pain [103][104][105][106].…”
Section: Dietary Supplements and Nutraceuticals: Friends Or Foes?mentioning
confidence: 99%
“…63 Further, a recent retrospective cohort study in older (>65 years of age) Veterans showed that muscle relaxants (including methocarbamol and cyclobenzaprine, among others) were associated with increased risk for emergency department visits as well as all-cause hospitalizations (including those for falls and fractures). 85 Another commonly used agent used for spasticity, and not included in the Beer’s criteria, is baclofen. Baclofen is a centrally acting skeletal muscle relaxant with an FDA indication to treat spasticity related to CNS lesions; dosing regimens vary by indication.…”
Section: Existing Guidelines For Managing Chronic Pain In Later Lifementioning
confidence: 99%